FIGURATIVE LANGUAGE IN HELLO MY NAME IS ALBUM BY BRIDGIT MENDLER - Dewi Wulan Sari (Asosiasi Dosen Muda Indonesia, 2022)
Figurative language is the linguistic devices that are used in order to make language more beautiful and interesting. The aims of this research are to find out the figurative languages found in Hello My Name Is Album by Bridgit Mendler and to find out the most dominant figurative language found in Hello My Name Is Album by Bridgit Mendler. This research used qualitative research method. This research used the theory of figurative language from Kennedy & Dana (1995). The data source of this research is Hello My Name Is Album. The data of this research is the lyrics that have figurative language in it. Out of 47 data found in this research, 14 data are simile, 10 data are metaphor, 11 data are personification, 7 data are overstatement, 2 data are metonymy, 1 data is synecdoche, 2 data are paradox. Based on the data collected, simile is the most dominant figurative language found in Hello My Name Is Album.